Jejak Kemanusiaan dalam Dialog Gereja dengan Kaum Migran dan Pengungsi di Keuskupan Maumere - Marianus Ronaldo Tiba; Hendrikus Nggala; Patrisius Rato; Polikarpus Beda Kaha; Afrianus Papak (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
This study explores the role of the Catholic Church in fostering dialogue with migrants and refugees in the Diocese of Maumere, Indonesia, while also examining its pastoral and theological responses to the complex challenges posed by modern migration. As migration becomes a pressing global issue, the Church is called to be a beacon of compassion, justice, and inclusion for those displaced from their homelands. Employing a qualitative research method, this study utilizes both fieldwork and literature review, with data gathered through in-depth interviews with clergy and community members, as well as analysis of ecclesiastical documents and pastoral guidelines.The findings reveal that the Church implements three primary forms of dialogue: the dialogue of presence, which emphasizes being physically and emotionally present with migrants; the dialogue of life, which promotes shared daily experiences and mutual respect; and the dialogue of liberation, which focuses on advocating for the rights and dignity of refugees. Despite these efforts, the Church faces several challenges, including limited financial and human resources, bureaucratic inefficiencies, and cultural resistance from segments of the local population.To address these obstacles, the study recommends that the Church strengthen collaboration with government agencies and civil society organizations, enhance education and empowerment initiatives for refugees, and promote community awareness on the values of solidarity and acceptance. By adopting a comprehensive and sustainable approach, the Church can reinforce its mission to serve the marginalized and uphold the inherent dignity of every human being, especially those most vulnerable due to forced migration and displacement.